Considering Nursing Theory Certification - Debra R. Hanna; Ellen B Buckner (Universidad de La Sabana, 2018)
Objective: A workshop to discuss development of nursing theory certifications at four levels of nursing knowledge was held as part of the 2016 annual conference of Roy Adaptation Association International. Method: Eight questions were discussed in small and large group formats. Discussion points hand recorded on a flip chart. These points are summarized in this article. Results: 35 international nurse scholars participated. They discussed benefits, limitations, and strategies of a new type of certification for nursing theory knowledge at four levels of education and practice. Conclusion: Nursing theory certification would affirm nursing knowledge, without becoming a burden to nurses. It can potentially affect how nurses are educated about theory at each of the four levels of education, how nurses use theory in practice, and the quality of nursing care provided. Continued dialog is warranted.